Sosialisasi Pemberian Makanan Tambahan Kepada Ibu Hamil di Posyandu Dahlia Kecamatan Abeli - Hartati Bahar; Hariati Lestari; Devi Savitri Effendy; Febriana Muchtar; Della Indriani; Hawila Seleng; Khalidah Izzatul Jannah; Rosalina Faiha Kirana (Lembaga Pengembangan Kinerja Dosen, 2025)
Pregnant women with poor nutritional status will experience nutritional imbalances that can lead to nutritional problems for pregnant women whose KEK is still higher than the WHO target. In an effort to meet the nutritional needs of mothers during pregnancy and increase the possibility of mothers giving birth to babies without LBW, PMT for pregnant women is one initiative to improve the nutrition of pregnant women. The highest number of Supplementary Food for pregnant women with KEK in Indonesia in 2023 was in West Papua, namely 139.2%, while the lowest was in West Java, namely 66.9%. One supplementation strategy to overcome nutritional problems is the provision of additional food (PMT), especially for vulnerable groups. The purpose of this socialization program is to increase awareness of pregnant women at the Dahlia Posyandu, Abeli District, about the importance of eating more to support their nutrition. Lectures accompanied by media, especially leaflets, are the techniques used. Twenty-five pregnant women attended this socialization. With statistical testing using the paired t-test, the results of the socialization showed that the average knowledge before and after receiving socialization and education was different, namely (p <0.05) or 0.000 <0.05. Therefore, it can be said that educating mothers about providing additional food (PMT) to pregnant women will help them become more knowledgeable.